Proposta do padrão oficial de classificação do açúcar mascavo: uma perspectiva ontológica - Godoy, José Luis Franco de (2024)
In Brazil, agricultural food products, whether domestic or imported, are regulated by the Ministry of Agriculture and Livestock through an official classification standard, according to the Federal Law No. 9.972:2000, ensuring consumer quality and safety, preventing fraud or imitation. Instruction Normative No. 47:2018, which classified crystalline and liquid sugars, excluded mascavo sugar, a product considered natural or gourmet and a potential economic source for family agriculture. Through qualitative bibliographic research, ontological analysis, and multivariate statistical analysis, the study aimed to develop a text for technical grounding of an official classification standard, characterizing mascavo sugar into classes and types. Sugarcane juice was defined as the raw material, with industrial and artisanal manufacturing processes, and intended for direct consumption. Quality parameters proposed were a minimum polarization of 84.0 °Z, maximum moisture content of 5.0%, maximum conductimetric ashes of 2.5%, and maximum reducing sugars of 8.0%. The inclusion in legislation of an exclusive class for mascavo sugar of granulated and amorphous types was proposed, which was evaluated and accepted by market agents involved in research, production, and commercialization of the product.